The polyphenol composition of Cistus incanus L., Trachystemon orientalis L. and Melissa officinalis L. infusions by HPLC-DAD method - Vanya Dimcheva; Nikolay Kaloyanov; Maria Karsheva (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
Because of plants, health benefi ts consumption of herbal infusions as a dietary additive has increased in the last years. The aim of the present study was to establish the individual phenolic profi les using highperformance liquid chromatography with diode-array detection (HPLC-DAD) method of Bulgarian Cistus incanus leaves harvested in summer and winter seasons, Cistus incanus hard-coated seeds, Greek Cistus incanus leaves harvested in summer, Bulgarian Trachystemon orientalis, and Melissa offi cinalis leave and stems extracts prepared as infusions.